2022
DOI: 10.1364/ao.456083
|View full text |Cite
|
Sign up to set email alerts
|

Design of a linear field-of-view oblique imaging system with a low distortion

Abstract: For conventional ultra-wide-angle or oblique cameras, it is difficult to fully correct the f − tan θ distortion without the scarification of the edge image performance. In this paper, we propose a linear field-of-view (FOV) oblique imaging system by varying the entrance pupil size over the FOV with freeform mirrors, and thus the diffraction limit around the edge field can be improved. An off-axis reflective system with conic surfaces has been selected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…However, distortion is unavoidable because there is an extremely wide-angle lens. Xu et al reported a freeform-mirrorbased oblique imaging system with linear field of view 35°~65° and <1.1% distortion [6]. A point-by-point surface design method was applied to obtain the initial optical system, and then all the surfaces were converted to freeform surfaces during the optimization process.…”
Section: Introductionmentioning
confidence: 99%
“…However, distortion is unavoidable because there is an extremely wide-angle lens. Xu et al reported a freeform-mirrorbased oblique imaging system with linear field of view 35°~65° and <1.1% distortion [6]. A point-by-point surface design method was applied to obtain the initial optical system, and then all the surfaces were converted to freeform surfaces during the optimization process.…”
Section: Introductionmentioning
confidence: 99%